COVID-19 VACCINE STRATEGIES IN INDONESIA AND THEIR RELATIONSHIP WITH NATIONAL RESILIENCE - Prabowo, Nurhasan Agung; Hartono; Suwandono, Adji (International Journal of Research -GRANTHAALAYAH, 2022)
National defence cannot be separated from the spectrum of threats faced by both military and non-military as well as the efforts made to overcome them. In line with that, national resilience is defined as the resilience of the nation and state in facing multidimensional challenges in planning its national interests. In general, the eight elements that support the achievement of Indonesia's national resilience are described in the Astagatra of National Resilience, which include aspects of geography, natural wealth, demography, ideology, politics, economy, socio-culture, defence, and security. Indonesia's national defence faces internal and external challenges; The current challenge is the Corona Virus Disease 19 (Covid-19) pandemic. Since the COVID-19 pandemic hit Indonesia, the government has continued to look for the most appropriate solution to reduce and break the chain of transmission of COVID-19, one of which is the provision of the COVID-19 Vaccine. This makes the government need to prepare a financing strategy for the procurement of COVID-19 vaccines. This study examines the Financing and Procurement of the COVID19 Vaccine in Indonesia. Researchers use library designs or research from several sources such as articles, news, regulations, official websites, and others located in Indonesia. The results of the study show that the Government of Indonesia must be prepared to finance the COVID-19 vaccine for as many as 182 million people, which is 70% of the total population. The government stipulates that funding for the COVID-19 vaccine procurement will be sourced from the State Revenue and Expenditure Budget and the Regional Revenue and Expenditure Budget. Based on the above context, this paper examines how the pandemic triggers the threat of food scarcity in Indonesia in a narrow sense and challenges the achievement of national security in a broad sense. This paper uses the Astagatra approach model to see how the Government of Indonesia responds to Covid-19 these challenges.